The Role Of Literature In Language Learning: Strategies For Improving Students' Literacy Skills In The Digital Age - Nainggolan, Zul Pahri (Jurnal Scientia, 2024)
The present study explores the potential of literature to enhance students' literacy skills in the digital era. Employing qualitative research methods, it delves into the efficacy of literary works, such as poems, short stories, and novels, as effective learning tools. The study sheds light on the ways these literary instruments can be utilized to cultivate a range of skills, including reading, writing, speaking, and critical thinking.The study's methodology comprises in-depth interviews with language teachers, classroom observations, and a thorough analysis of learning documents. The data gathered through these methods serves to inform and substantiate the argument put forth. The study's findings suggest that integrating literature into language instruction can foster students' engagement with reading material and facilitate comprehension of both cultural and social context. Moreover, leveraging digital technology has been shown to expand access to literary resources, enhancing collaborative learning opportunities and promoting interactive engagement.